(untitled) (Global Journal of Human-Social Science, 2022)
Love and sexuality are analyzed in everyday experiences and in religious secular discourses as long-term power strategies in western patriarchy seeking to verify the dialectic established between legislation and social practices in Brazil In the search for answers the investigation focuses on two complementary but distinct instances the presence of love and sexuality in the collective imagination and how this imaginary which circulates between us and around us interests power and institutions It appears that the legal bases of western legislation and its effects are structuring elements of prescribed or proscribed sexual behaviors according to a logic that opposes desires to duties creating a pastoral of fear